2016
DOI: 10.1177/2156587215627551
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prayer on Intensity of Migraine Headache

Abstract: Background and Aim. Migraine is a common form of headache that affects patients quality of life negatively. In addition to pharmacologic treatment, there are a variety of nonpharmacologic treatments for migraine headache. In present study, we examined the effect of prayer on intensity of migraine pain. Methods. In a prospective, randomized, controlled trial from October 2013 to June 2014, this study has been conducted in Kerman, Iran. We randomly assigned 92 patients in 2 groups to receive either 40 mg of prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 21 publications
0
22
1
Order By: Relevance
“…Specifically, intercessory prayer has been shown to improve migraine pain. (26) Further, Jegindo and colleagues found that for religious pain-free individuals, prayer was associated with decreased pain intensity and unpleasantness during an electrical stimulation task. (27,28)…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, intercessory prayer has been shown to improve migraine pain. (26) Further, Jegindo and colleagues found that for religious pain-free individuals, prayer was associated with decreased pain intensity and unpleasantness during an electrical stimulation task. (27,28)…”
Section: Introductionmentioning
confidence: 99%
“…Based on the evidence of previous research of small to large effects of HYP, MM, and CP on pain intensity and pain tolerance, we considered a small effect size (Cohen’s f ) of 0.15 for a Time × Condition interaction effect as well as a two-sided α of 0.05 and a power of 0.95. 24 , 26 , 27 , 50 , 52 , 53 This calculation resulted in a minimum sample size required to detect a Time × Condition interaction effect of 196 participants (49 per study condition).…”
Section: Methodsmentioning
confidence: 99%
“…Using experimental designs, prayer has been associated with reduced pain and healthier cardiovascular responses to stress. For instance, in a randomized clinical trial of the effects of prayer on migraine headaches among Muslim patients, pain was significantly lower in the group who received pharmacological treatment plus prayer for 2 months than the group who received only pharmacological treatment for 2 months (Tajadini et al, 2017). Similarly, in a meditation study of migraine sufferers, compared to three other groups (internally focused secular meditation, externally focused secular meditation, progressive muscle relaxation), those who practiced spiritual meditation had greater decreases in the frequency of migraine headaches, anxiety, and negative affect, as well as greater increases in pain tolerance, headache-related selfefficacy, daily spiritual experiences, and existential well-being (Wachholtz & Pargament, 2008).…”
Section: Prayermentioning
confidence: 99%